Active methodologies from an innovative vision (Research, Society and Development, 2022)
This research addresses the insertion of active methodologies in higher education, focusing on an innovative vision. In this perspective, we seek to answer the following question: what steps does an active methodology need to develop in order to welcome a vision of complexity, with the role of students? Its objectives are: (i) to identify the relationship between active methodologies and the theory of complexity proposed by Morin; (ii) to investigate how the doctoral students of a postgraduate program involved in the research understand the active methodologies, based on the theory of complexity proposed by Morin. Therefore, a qualitative approach was carried out in a graduate program of a large university in the city of Curitiba, Paraná, using as a research instrument the application of an online questionnaire to seven doctoral students of the aforementioned program. It was possible to identify that active methodologies have been gaining ground in the academic environment and that, when used with a focus on an innovative perspective, they contribute to the construction of students' autonomy, as well as responsibility and interaction between peers.